Mendesain Pembelajaran Kreatif melalui Penerapan Flipped Classroom: Pengabdian - Takdir, Muh.; Listyasari, Winda Dewi; Mayasari, Linda Ika; Kamaludin, Kamaludin; Ramadhan, Nabil Auliya; Jahudin, Andi Aswad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aimed to enhance the capacity of teachers at Ma’had Al-Istiqlal Foundation, Karawang, in designing creative learning through the implementation of the flipped classroom model. This model was selected because it aligns with student-centered learning approaches and has the potential to foster more meaningful classroom interactions. The implementation methods included the dissemination of flipped classroom concepts, technical training in the preparation of learning materials, mentoring in lesson design practices, and evaluation of program outcomes. The results indicate a significant improvement in teachers’ understanding of flipped classroom principles, their ability to develop pre-class learning materials (videos and digital modules), and their planning of in-class activities emphasizing higher-order thinking skills. Moreover, teachers demonstrated positive attitudinal changes toward instructional innovation, becoming more enthusiastic and confident about implementing this approach in their respective classrooms. Institutional support from the foundation, such as providing technological facilities and establishing teacher learning communities, further strengthened the program’s impact. This activity is expected to serve as a starting point for transforming teaching and learning at Ma’had Al-Istiqlal as well as a model of best practice for other educational institutions.